Metabolic engineering in lignocellulose biorefining for high-value chemicals: recent advances, challenges, and outlook for enabling a bioeconomy - Lama, Suman; Thapa, Laxmi Prasad; Upadhayaya, Subodh Kumar; Gauchan, Dhurva Prasad; Singh, Anjana (Frontiers in Industrial Microbiology, 2024)
Lignocellulose biomass presents a promising and renewable alternative to fossil fuels. Numerous engineered microorganisms have been developed to efficiently utilize this biomass and convert it into valuable platform chemicals. This article provides an overview of the extensive metabolic engineering strategies employed to create robust microbial cell factories for lignocellulose biorefinery. The focus lies on the production of various chemicals including succinic acid, lactic acid, 3-hydroxypropinic acid, xylitol, biohydrocarbons, itaconic acid, 2-phenylethanol, 1,2,4-butanetriol, and 2,3-butanediol from lignocellulose hydrolysate, especially hemicellulose. Additionally, the article briefly discusses the techno-economic analysis, challenges, and future prospects for achieving more sustainable production of these chemicals.